The tonoplast-localized transporter OsHMA3 plays an important role in maintaining Zn homeostasis in rice. (6th March 2019) - Cai, Hongmei; Huang, Sheng; Che, Jing; Yamaji, Naoki; Ma, Jian Feng
Abstract : A tonoplast-localized OsHMA3 plays an important role in Zn detoxification at high concentrations and in storage under Zn-limited conditions through sequestration into the vacuoles in roots of rice. Abstract: In order to respond to fluctuating zinc (Zn) in the environment, plants must have a system to control Zn homeostasis. However, how plants maintain an appropriate level of Zn during their growth and development is still poorly understood. In this study, we found that OsHMA3, a tonoplast-localized transporter for Zn/Cd, plays an important role in Zn homeostasis in rice. Accessions with the functional allele of OsHMA3 showed greater tolerance to high Zn than those with the non-functional allele based on root elongation test. A 67 Zn-labeling experiment showed that accessions with loss of function of OsHMA3 had lower Zn accumulation in the roots but similar concentrations in the shoots compared with functional OsHMA3 accessions. When exposed to Zn-free growing medium, the concentration in the root cell sap was rapidly decreased in accessions with functional OsHMA3, but less dramatic changes were observed in non-functional accessions. A mobility experiment showed that more Zn in the roots was translocated to the shoots in accessions with functional OsHMA3 . Higher expression levels of OsZIP4, OsZIP5, OsZIP8, and OsZIP10 were found in the roots of accessions with functional OsHMA3 in response to Zn deficiency. Taken together, our results indicate that OsHMA3 plays an important role in rice roots in both Zn detoxification and storage by sequestration into the vacuoles, depending on Zn concentration in the environment.